GUIDANCE study: guided growth of the proximal femur to prevent further hip migration in patients with cerebral palsy—study protocol for a multicentre randomised controlled trial - Max Reijman; Denise Eygendaal; M Adhiambo Witlox; Renée Anne van Stralen; Merel Charlotte Rosalie Roelen; Sophie Moerman; Melinda Maria Eva Helena Witbreuk; Arno ten Ham; Jaap Johannes Tolk (BMJ Open)
Introduction Up to one-third of patients with cerebral palsy (CP) develop hip migration. Current standard care for early hip migration is bilateral adductor-psoas tenotomy; however, the failure rate is relatively high with 34%–74% of patients with CP requiring secondary hip surgery. Using temporary medial hemiepiphysiodesis of the proximal femur (TMH-PF), the morphology of the hip can be changed. This technique aims to reduce further hip migration and the need for secondary surgical management. Further research is necessary to determine the benefit of TMH-PF in addition to adductor-psoas tenotomy. The hypothesis of this study is that TMH-PF combined with adductor-psoas release decreases the chance of progressive hip migration and the need for secondary hip surgery, compared with adductor-psoas release alone.Methods and analysis The GUIDANCE study is an open-label multicentre randomised controlled trial. Patients with CP aged between 2 and 8 years, with spastic CP—Gross Motor Function Classification System IV or V, hip abduction ≤40° and hip migration of 30%–50% can be included in this trial. They will be randomised into a control arm (adductor-psoas tenotomy) or an intervention arm (adductor-psoas tenotomy+TMH PH). The primary outcome will be treatment failure at 5-year follow-up. At 2-year follow-up a preliminary analysis will be performed. Secondary outcomes will be differences in patient-reported outcome measures (CPCHILD and CPG pain score), range of motion, radiological measurements including head shaft angle and hip migration percentage and three-dimensional (3D) morphological changes to the proximal femur. Furthermore, an analysis will be performed to identify predictors for treatment failure in both treatment arms.Ethics and dissemination The GUIDANCE study should provide evidence on the effectiveness of TMH-PF in addition to adductor-psoas tenotomy in children with CP with early hip migration. If beneficial, larger hip reconstructive procedures can be delayed or prevented, providing a distinct benefit for these vulnerable children. The study’s strengths lie in its methodological framework, incorporating randomised allocation and intervention assessment. The main limitation is the inability to blind the treating physician or the researcher for the treatment arm the participant is allocated to. The results of the GUIDANCE study will be presented at scientific meetings and published in international peer-reviewed journals. The aim is to publish the results at 2 years follow-up and 5 years follow-up and to publish the results of the analysis on the 3D morphology of the hip after TMH-PF. Individual de-identified participant data that underlie the results from the GUIDANCE study and the study protocol will be shared if requested.Trial registration number Clinical Trial Registry number: NCT06118736. Registered on 3 November 2023.